Betatron radiation and emittance growth in plasma wakefield accelerators. (24th June 2019) - San Miguel Claveria, P.; Adli, E.; Amorim, L. D.; An, W.; Clayton, C. E.; Corde, S.; Gessner, S.; Hogan, M. J.; Joshi, C.; Kononenko, O.; Litos, M.; Lu, W.; et al.
Abstract : Beam-driven plasma wakefield acceleration (PWFA) has demonstrated significant progress during the past two decades of research. The new Facility for Advanced Accelerator Experimental Tests (FACET) II, currently under construction, will provide 10 GeV electron beams with unprecedented parameters for the next generation of PWFA experiments. In the context of the FACET II facility, we present simulation results on expected betatron radiation and its potential application to diagnose emittance preservation and hosing instability in the upcoming PWFA experiments. This article is part of the Theo Murphy meeting issue 'Directions in particle beam-driven plasma wakefield acceleration'.